(untitled) (Global Journal of Management and Business Research, 2024)
The increasing incidence of cybercrimes has become a pressing issue for society businesses and governments Responding to the growing demand for digitisation from customers and investors South African institutions have become targets of sophisticated cyberattacks The financial sector considered part of the country s critical infrastructure has not been immune The frequency of attacks on commercial banks in South Africa has risen with several successful cyberattacks causing substantial harm This paper explores the interventions commercial banks use in South Africa through a qualitative research lens The results indicate that while technical interventions provide value there are still opportunities for improvement in the human and process elements of the interventions This highlights the need for a holistic approach to cybersecurity incorporating technology people and processes to mitigate the risks posed by cyber threats effectively